2017
DOI: 10.1186/s12877-017-0487-3
|View full text |Cite
|
Sign up to set email alerts
|

Setting-related influences on physical inactivity of older adults in residential care settings: a review

Abstract: BackgroundDespite the detrimental effects of physical inactivity for older adults, especially aged residents of residential care settings may spend much time in inactive behavior. This may be partly due to their poorer physical condition; however, there may also be other, setting-related factors that influence the amount of inactivity. The aim of this review was to review setting-related factors (including the social and physical environment) that may contribute to the amount of older adults’ physical inactivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 38 publications
5
23
0
Order By: Relevance
“…The results of this study further indicated that an additional PS may have effects on improvement of frailty status and body composition among frail older individuals undergoing exercise training sessions, regardless of the supplementation dose and exercise training type. In agreement with previous reviews [63,64] and following the recommendations from the European Society for Clinical Nutrition and Metabolism Expert Group [65], the results of the current meta-analysis supported the urgent necessity for prefrail or frail older adults to incorporate protein-based nutrition intervention plus exercise training to prevent functional decline, especially for institutionalized residents who are at a high risk of insufficient protein intake and physical inactivity [66,67,68,69].…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study further indicated that an additional PS may have effects on improvement of frailty status and body composition among frail older individuals undergoing exercise training sessions, regardless of the supplementation dose and exercise training type. In agreement with previous reviews [63,64] and following the recommendations from the European Society for Clinical Nutrition and Metabolism Expert Group [65], the results of the current meta-analysis supported the urgent necessity for prefrail or frail older adults to incorporate protein-based nutrition intervention plus exercise training to prevent functional decline, especially for institutionalized residents who are at a high risk of insufficient protein intake and physical inactivity [66,67,68,69].…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, active seniors tend to display lower R and higher PhA [ 47 , 48 , 49 ]. Older people living in institutions are usually characterized by a lower level of PA in comparison with CD subjects [ 50 ]. What is more, institutionalization influences not only leisure PA but also usual daily living activities.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature suggests that social and physical inactivity in RACFs can be explained by a range of interdependent factors including: patient-related, such as immobility; organisational, such as lack of meaningful activities; environmental, concerning the facilities in the ward; and caregiver-related, including staffing levels, time constraints and type of care given [9,46]. In addition, we found that social and physical inactivity is to a large extent influenced by management- & government-related factors that shape and influence the other factors.…”
Section: Introductionmentioning
confidence: 99%